Biparietal osteodystrophy in an 86-year-old woman: an incidental finding following minor head trauma - Ruzman, Nur Hanani; Koo, Thai Hau; Ibrahim, Idris; Huddin, Azzam Baseri; Zakaria, Andee Dzulkarnaen; Ahmad Saad, Fathinul Fikri; Zakaria, Mohd Hazeman (Elsevier, 2025)
Biparietal osteodystrophy (bilateral parietal bone thinning) is a rare but well-documented phenomenon characterized by symmetric thinning of the parietal bones of the skull. It predominantly affects older adults, particularly women. We report the case of an 86-year-old woman who was incidentally diagnosed with this condition after a minor head injury. She presented with a low-impact fall and underwent neuroimaging to exclude intracranial hemorrhage. Computed tomography (CT) of the head revealed bilateral concave thinning of the parietal bones with an intact inner table, and no acute fracture or hemorrhage. A comprehensive workup, including metabolic and endocrine tests, showed no secondary causes of bone loss. Neurosurgical evaluation confirmed that no intervention was required. The patient was managed conservatively and advised on fall prevention measures, given the increased risk of skull fracture and brain injury in the presence of severe calvarial thinning. This case highlights the importance of recognizing biparietal osteodystrophy on imaging and distinguishing it from more acute pathologies as well as the need for appropriate counseling regarding its clinical implications.